A comparison of intervention and conservative treatment for angulated fractures of the distal forearm in children (AFIC): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Adrian, Miriam; Wachtlin, Daniel; Kronfeld, Kai; Sommerfeldt, Dirk; Wessel, Lucas
Abstract Background Angulated fractures of the distal forearm are very frequent lesions in childhood. Currently, there are no standard guidelines on whether these children should be treated conservatively with a cast; with reduction and a cast; or with reduction, pinning and a cast under anesthesia. Minor prospective and retrospective studies have shown that the distal physis of the forearm possesses high remodeling capacity leading to reliable correction of malalignment. The aim of this trial is to answer the question about whether operative and conservative treatment show equivocal results. Methods/Design This is a prospective, multinational, multicenter, randomized, observer-blinded, actively controlled, parallel group trial, with 24 months of observation. The primary objective of this trial is to assess whether or not the long-term functional outcome in remodeling patients is inferior to patients receiving closed reduction and K-wire pinning. The trial should include 742 patients with acute fracture. The patients will be included in 30 medical centers in Germany, Switzerland and Austria. All patients 5 to 11 years of age presenting at the emergency department with an angulated distal fracture of the forearm will be randomized online after informed consent. The primary endpoint is the Cooney Score after 24 months. The secondary endpoint is the grade of radiological displacement at 12/24 months. Discussion Therapy of angulated fractures is a matter of intensive debate. Primary manipulation and pinning under general anesthesia is recommended in order to avoid malalignment. No major study has proven the advantage of manipulation and pinning over immobilization alone. Should remodeling appear to be a safe alternative, manipulation under general anesthesia, K-wire pinning and removal of pins could be avoided, thus sparing significant costs. Trial registration DRKS00004874, 30 October 2013.